PREVENTIVE MEASURES AGAINST INFECTION WITH THE CORONA EPIDEMIC IN THE ISLAMIC PERSPECTIVE - Mazin Rabee Mohammad Al-nayil, Prof. Dr. Majeed Saleh Ibrahim Al-Qaisi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Praise be to God who singled out affliction, and blessings and peace be upon our Prophet Muhammad and all his family and companions, and after ... There is no blame. The task of man in this world is affliction, so the earth has made an arena for this struggle, whose Sharia ruler should be under divine oversight, and this continues until every nation reaches its deadline, at which time the war ends, in order for the differential points to be calculated to show which one is better. Among the images of the affliction is this epidemic, which spread its wings all over the earth and covered and covered the shadow of fear that accompanies the souls of people. But one of the grace of God Almighty over the nation of Islam is that he provided us with knowledge of what was meant by the affliction, to be an expiation for what sins past and an exhortation for what is received. The necessity of building a quarantine fence when epidemics occur and adopting safety reasons. From what has been mentioned above, the many aspects of anyone who wants to write regarding the Corona epidemic become clear , and I have been destined to write on the topic " Preventive measures against infection with the Corona epidemic in the Islamic perspective . "